Vienna's Dorotheum: A singular auction house and hockshop. - Dornberg, John (Smithsonian)
Celebrates Vienna's Dorotheum, the state owned and operated auction house and pawn brokerage. How business is conducted at the institution; Ground rules and peculiarities of the business; Dorotheum's history and founding.